Using the Visual to Address Gender-Based Violence in Rural South Africa: Ethical Considerations (LEARNing Landscapes, 2016)
Violence against women and girls (VAW) is a critical issue of global importance. Research suggests that indigenous girls and young women from resource-poor, rural communities are particularly susceptible to VAW and yet, few studies directly target this vulnerable population group due to ethical considerations. We present some emerging ndings from rural KwaZulu-Natal, South Africa, where we are using participatory visual research with girls and young women to investigate VAW in this context. Our results suggest while ethical issues may arise in the application of participatory visual tools in contexts of vulnerability, it is still possible to proceed without harm and to gain pertinent insight into this important issue.
Keywords: Violence against women and girls (VAW); participatory research; visual; vulnerability; community